Muerte cerebral o muerte encefálica. La muerte es una sola - Díaz T., Violeta (Revista Hospital Clínico Universidad de Chile, 2009)
Historic aspects are described of the concept of death and alter brain death. We analyzed definition and characteristics of coma without answer, cerebral trunk activity absence. They are described and details the execution of the test of apnea and its limits. It is analyzed some differential diagnostics and movements that can be found in brain death. Some complementary exams are indicated and by finalize legal aspects are discussed.